Load Invariant CC and CV Modes for Static/Dynamic Wireless Charging System With Half-Bridge Multi-Leg Converter Topology - Aganti Mahesh; Bharatiraja Chokkalingam; Rajesh Verma; Lucian Mihet-Popa (IEEE Access)
Resonant Inductive Power Transmission (RIPT) is an advanced Wireless Power Transfer (WPT) technology, emerging as a secure and efficient solution for Electric Vehicle (EV) charging. Although Dynamic Wireless Charging Systems (DWCS) reduce the need for large batteries compared to static charging, they require higher initial investments. This study introduces a novel approach utilizing LCC-S compensation to achieve load-invariant Constant Current (CC) and Constant Voltage (CV) outputs at two distinct Zero Phase Angle (ZPA) frequencies in DWCS, leveraging a half-bridge-based multi-legged inverter configuration. The article presents a new method with fewer iterations to determine the optimal compensation parameters, ensuring that both the CC and CV outputs with ZPA comply with the SAE J2954 frequencies standards. The half-bridge-based DWCS with LCC-S compensation is designed to operate in either CC or CV mode, depending on whether the application involves static or dynamic charging. A 1-kW LCC-S compensated DWCS prototype was developed and built to verify and support the theoretical findings and analysis. This study offers valuable insights for optimizing RIPT technology, making EV charging more efficient and cost-effective.